PUF-8 and MPK-1: Genetic and Chemical Control of Spermatocyte Dedifferentiation in Caenorhabditis elegans - Gaddy, Matthew A. (East Carolina University, 2021)
Stem cells face a number of major fate decision during their development: the decision to self-renew or differentiate, and then whether to remain differentiated or dedifferentiate, as occurs in some oncogenesis. A regulatory network controlling these decisions is vital to the development of all multicellular organisms, including humans. Aberrant regulation can result in either loss of specific cell type or uncontrolled cell proliferation, leading to tumors. However, our understanding of how differentiated cell can be reverted to an undifferentiated state remains far more limited.Using the nematode C. elegans germline as a model system, we previously reported that PUF-8 (a PUF RNA-binding protein) and LIP-1 (a dual-specificity phosphatase) inhibit the formation of germline tumors via repressing the dedifferentiation of spermatocytes into mitotic cells (termed "spermatocyte dedifferentiation") at least in part by inhibiting MPK-1 (an ERK MAPK homolog) activation. To gain insight into the molecular competence for spermatocyte dedifferentiation, we compared the germline phenotypes between two competent mutants -- puf-8(q725); lip-1(zh15) with a high MPK-1 activity and puf-8(q725); fem-3(q20gf) with a low MPK-1 activity. puf-8(q725); lip-1(zh15) mutants developed germline tumors more aggressively than puf-8(q725); fem-3(q20gf) mutants at 25°C with aging. This result suggests that MPK-1 activation is critical to induce the formation of germline tumors via spermatocyte dedifferentiation. This idea was confirmed by treatment of puf-8(q725); fem-3(q20gf) mutant worms with Resveratrol, which stimulates MPK-1 activation. Our results show that 100 mM RSV significantly induced the formation of germline tumors via spermatocyte dedifferentiation at 25°C with aging. Therefore, we conclude that MPK-1 activation is required to promote the formation of germline tumors via spermatocyte dedifferentiation in the absence of PUF-8. Since PUF-8 and MPK-1 are broadly conserved, we therefore suggest that similar molecular mechanisms may control dedifferentiation-mediated tumorigenesis in other organisms, including humans.
Keywords: Differentiation; Dedifferentiation; Tumorigenesis; MPK-1; PUF-8; Germline; Resveratrol; Spermatocytes; Caenorhabditis elegans; Animals; Caenorhabditis elegans Proteins